151k views
3 votes
Solve the following quadratic equation using the quadratic formula. Separate multiple answers with a comma if necessary. −6x^2+1=−2x

1 Answer

5 votes

Answer:

Explanation:

Hello,

We just need to apply the formula using the discriminant


-6x^2-2x+1=0\\\\\Delta = b^2-4ac = (-2)^2-*4(-6)*1=4+24=28

so we have two distinct real solutions


x_1=(2+√(28))/(2*(-6))=(2+2√(7))/(2*(-6))=-(√(7)+1)/(6) \\\\ and \\\\x_2=(√(7)-1)/(6)

Hope this helps

User Alex Fragotsis
by
4.8k points